DEVELOPMENT DIRECTIONS OF THE LIFE INSURANCE SECTOR - Matiyazova Sanobar Rajabbayovna (Bright Mind Publishing, 2025)
This article outlines the economic essence and significance of life insurance, analyzes the current state and trends in the life insurance sector within the insurance market of Uzbekistan, and explores the directions for the development of thissector.
Keywords: Insurance market, life insurance, insurance premiums, insurance payouts, financial analysis of insurance companies, insurance products, insurance business, innovations.